Susceptibility of zoopathogenic fungi to phytoalexins. - Gordon, M A (1980)
Phytoalexins are a group of low-molecular-weight antibiotics produced by higher plants in response to infection by relatively avirulent microorganisms. They are of relatively low toxicity for mammalian cells and have been reported to possess a broad spectrum of antimicrobial activity against bacteria and phytopathogenic fungi. Employing a broth dilution technique, we have found the zoopathogens Petriellidium boydii, Aspergillus flavus, A. fumigatus, Candida albicans, Coccidioides immitis, Cryptococcus neoformans, Histoplasma capsulatum, Rhizopus oryzae, Sporothrix schenckii, and Trichophyton rubrum to be inhibited by one or more of the phytoalexins maackiain, medicarpin, phaseollin, phaseollin isoflavan, pisatin, sativan, and vestitol in concentrations of from 12.5 to 50 microgram/ml. Phaseollin isofalvan was the most effective of these. In agar cup diffusion tests growth of the yeast form of Blastomyces dermatitidis was inhibited by phaseollin at 50 microgram/ml and by phaseollin isoflavan at 25 microgram/ml. Susceptibility of the mycelial form of B. dermatitidis to these two compounds was demonstrated by inhibition of radial extension on agar plates.